Inclusive Education Model in Special Needs Friendly Secondary Schools: Model Pendidikan Inklusif di Sekolah Menengah Ramah Siswa Berkebutuhan Khusus - Ali Fauzi; Tobroni; Joko Widodo (Universitas Muhammadiyah Sidoarjo, 2025)
AbstractInclusive education aims to create equitable and supportive learning environments for all students, including those with special needs (SEN). At the secondary school level, the implementation of inclusive practices presents more complex challenges compared to primary education, such as diverse learning needs and the risk of discrimination or bullying. Previous studies have primarily focused on primary education or curricular aspects, with limited attention to adaptive and contextual service models suitable for secondary schools. This article seeks to explore and describe a student-friendly inclusive education model through the integration of cluster and pull-out approaches, combined with community-based anti-bullying strategies. The findings indicate that combining cluster and pull-out models provides flexible and adaptive learning spaces while maintaining opportunities for SEN students to engage in social interactions within regular classrooms. This strategy is further strengthened by the use of Individualized Education Programs (IEP) and alignment with the Universal Design for Learning (UDL) framework. The study proposes a conceptual model that integrates service approaches, adaptive curricula, and social strategies to support the learning success of SEN students in secondary schools. These findings offer practical guidance for schools and policymakers in promoting fair, inclusive, and stigma-free secondary education.Highlight : Dual Strategy Approach: Combines cluster and pull-out models to support learning needs of students with disabilities in inclusive classrooms. Contextual Adaptation: Emphasizes the need for flexible strategies in secondary schools due to the complexity of adolescent development. Global Alignment: Integrates Universal Design for Learning (UDL) and Index for Inclusion to meet international standards in inclusive education. Keywords : Inclusive Education, Secondary School, Special Needs Students, Cluster Model, Pull-Out Strategy